2015
DOI: 10.1371/journal.pone.0141963
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Effects of Voice Disorders among Secondary School Teachers in Peninsular Malaysia Using a Validated Malay Version of VHI-10

Abstract: ObjectivesTo establish the prevalence of voice disorder using the Malay-Voice Handicap Index 10 (Malay-VHI-10) and to study the determinants, quality of life, depression, anxiety and stress associated with voice disorder among secondary school teachers in Peninsular Malaysia.MethodsThis study was divided into two phases. Phase I tested the reliability of the Malay-VHI-10 while Phase II was a cross-sectional study with two-stage sampling. In Phase II, a self-administered questionnaire was used to collect socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 37 publications
3
50
0
10
Order By: Relevance
“…In contrary, our study revealed that the gender determinant had no significant association, which was supported by the similar findings by Moy et al (2015) in Malaysia among secondary school teachers.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In contrary, our study revealed that the gender determinant had no significant association, which was supported by the similar findings by Moy et al (2015) in Malaysia among secondary school teachers.…”
Section: Discussionsupporting
confidence: 73%
“…In a recent research conducted among secondary schools teachers in Malaysia, Moy et al, (2015) found a higher prevalence of voice disorders (10.4%) utilizing the similar research tool, which makes this a good point of comparison. The higher prevalence may be explained by the disproportion Sundram, R. E., Bachok, A. N., Ibrahim, I. M., Husain, N. R. N., Mohamad, H., Moy, M. F. & Shafei, N. M. (2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Presence of LPR can be detected by Reflux symptom index questionnaire which contain 9 questions about past month symptoms of reflux [10]. Smoking, caffeine intake, voice abuse, noisy background, history of trauma or surgery and female gender are all considered risk factors for voice disorders [5][6][7][8][9][10][11]. Although a trial of proton pump inhibitors has been suggested to be cost-effective for treatment and diagnosis of LPR.…”
mentioning
confidence: 99%
“…Todos os resultados de que trataram os 15 artigos se basearam em estudos transversais. Trata-se de um desenho adequado, ainda que não autorize a inferência causal sobre a prevalência de doenças e fatores associados 13,15 . Os resultados dos estudos transversais são valiosos ao sugerir associações que permitem explorar hipóteses plausíveis, as quais, por sua vez, suscitam aprofundamento das investigações.…”
Section: Discussionunclassified